Outcomes of tuberculous meningitis in children: a case review study - Yazid Dimyati; Anna Tjandradjani; Irawan Mangunatmadja; Dwi Putro Widodo; Hardiono D. Pusponegoro (Paediatrica Indonesiana, 2011)
Background Tuberculous meningitis is a severe extrapulmonary complication of tuberculosis, with high morbidity and mortality rates.Objective To assess the relationship between presenting clinical characteristics and outcomes of pediatric tuberculous meningitis.Methods We present a case review study of all children diagnosed with tuberculous meningitis in Cipto Mangunkusumo Hospital, Jakarta between January 1998 and December 2004. We compared demographic, clinical, and diagnostic characteristics to clinical outcomes.Results We included 43 patients. Common characteristics on admission were young age (mean 3.2 years), stage II and III tuberculous meningitis (91%), and neurological symptoms existing for more than 1 week, including convulsions (52%), unconsciousness (23%), meningeal irritation (56%), and cranial nerve palsy (67%). A common feature of tuberculous meningitis on computed tomography scan of the brain was hydrocephalus in 19/24 cases. Clinical outcomes were neurological sequelae (88%) and death (12%). Factors associated with poor outcome in univariate analyses were young age, as well as stage II and III tuberculous meningitis.Conclusions Tuberculous meningitis starts with nonspecific symptoms and is often only diagnosed when brain damage has already occurred. Outcome is directly associated with age and the stage of tuberculous meningitis. Earlier diagnosis may significantly improve outcomes. [Paediatr Indones. 2011;51:288-93].